2020
DOI: 10.1002/smll.202004208
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐Enhanced Magnetism in Exfoliated Atomically Thin Magnetite Sheets

Abstract: It had been found that spinorbit coupling components were small in FeO systems, [44,45] therefore collinear spin model was used in the magnetene layers. The Brillouin zone integrations for the bulk and slab were carried out on a converged Monkhorst pack k-mesh of sizes 3 × 3 × 3 and 4 × 6 × 1, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…Correspondingly, the magnetene O1s peak confirms this reduced valence showing a predominance of Fe 2+ -O, while the Fe 3+ -O peak is diminished. This indicates that, upon confinement, the collective valence state is reduced from the bulk Fe 2.48+ to Fe 2.19+ , which is in agreement with previous DFT calculations that showed a decrease from +1.25 |e| at the Fe octahedral site (mixed Fe 2+ and Fe 3+ ) to +1.1 |e| ( 7 ). The second predominant difference that can be noted by the XPS spectra is the O1s signal.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Correspondingly, the magnetene O1s peak confirms this reduced valence showing a predominance of Fe 2+ -O, while the Fe 3+ -O peak is diminished. This indicates that, upon confinement, the collective valence state is reduced from the bulk Fe 2.48+ to Fe 2.19+ , which is in agreement with previous DFT calculations that showed a decrease from +1.25 |e| at the Fe octahedral site (mixed Fe 2+ and Fe 3+ ) to +1.1 |e| ( 7 ). The second predominant difference that can be noted by the XPS spectra is the O1s signal.…”
Section: Resultssupporting
confidence: 91%
“…1, A, D, G, and H ) ( 6 ), magnetene (Fe 3 O 4 ; Fig. 1, B, E, H, and I ) ( 7 ), and chromiteen (FeCr 2 O 4 ; Fig. 1, C, F, I, and L ) ( 8 ) are 2D iron oxide nanomaterials that can be cleaved by liquid sonication exfoliation along their respective weak planes, producing uniform atomic layers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Balan et. al., reported that natural mineral specimens can be ultrasonically exfoliated in a solvent to yield ultra-thin sheets that they called 'hematene' [3] or 'magnetene' [4]. Other authors previously synthesised magnetic half-unit-cell thick α-Fe2O3 nanosheets from a goethite precursor, using template-assisted oriented growth [5].…”
Section: Introductionmentioning
confidence: 99%